Koncepcja "Społeczeństwa wychowującego" i ciągłej edukacji w realiach współczesnej szkoły = The idea of upbringing society and permanent education in modern school - Arleta Magdalena Rogozińska; Małgorzata Karwowska; Justyna Rybicka; Mariusz Klimczyk (Kazimierz Wielki University, 2015)
Rogozińska Arleta Magdalena, Karwowska Małgorzata, Rybicka Justyna, Klimczyk Mariusz. Koncepcja "Społeczeństwa wychowującego" i ciągłej edukacji w realiach współczesnej szkoły = The idea of upbringing society and permanent education in modern school. Journal of Education, Health and Sport. 2015;5(8):337-342. ISSN 2391-8306. DOI 10.5281/zenodo.29066 http://dx.doi.org/10.5281/zenodo.29066 http://ojs.ukw.edu.pl/index.php/johs/article/view/2015%3B5%288%29%3A337-342 https://pbn.nauka.gov.pl/works/611806 POL-index https://pbn.nauka.gov.pl/polindex/browse/article/article-b5767c3d-a1f7-4d35-9a07-54606e4aa94f Formerly Journal of Health Sciences. ISSN 1429-9623 / 2300-665X. Archives 2011-2014 http://journal.rsw.edu.pl/index.php/JHS/issue/archive   Deklaracja. Specyfika i zawartość merytoryczna czasopisma nie ulega zmianie. Zgodnie z informacją MNiSW z dnia 2 czerwca 2014 r., że w roku 2014 nie będzie przeprowadzana ocena czasopism naukowych; czasopismo o zmienionym tytule otrzymuje tyle samo punktów co na wykazie czasopism naukowych z dnia 31 grudnia 2014 r. The journal has had 5 points in Ministry of Science and Higher Education of Poland parametric evaluation. Part B item 1089. (31.12.2014). © The Author (s) 2015; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland and Radom University in Radom, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 15.07.2015. Revised 21.08.2015. Accepted: 23.08.2015.   Koncepcja "Społeczeństwa wychowującego" i ciągłej edukacji w realiach współczesnej szkoły The idea of upbringing society and permanent education in modern school   Arleta Magdalena Rogozińska, Małgorzata Karwowska, Justyna Rybicka, Mariusz  Klimczyk   Kazimierz Wielki University in Bydgoszcz, Poland   Streszczenie   W artykule poruszono problem kształcenia ustawicznego osób dorosłych. Dokonano próby analizy porównawczej w zakresie edukacji dorosłych w celu podniesienia wykształcenia i kwalifikacji zawodowych i kształcenia ustawicznego nauczycieli. Dostrzeżono potrzebę doskonalenia warsztatu nauczyciela w szybko zmieniającym się świecie, w którym człowiek musi zmienić dotychczasowe myślenie o sobie i zbudować w  sobie pokłady motywacji do ciągłej pracy nad sobą, aby być. Słowa kluczowe: społeczeństwo wychowujące, edukacja ustawiczna.   Abstract   The article addresses the issue of lifelong learning for adults. An attempt was made a comparative analysis of adult education in order to improve educational and professional qualifications and continuing education of teachers. Workshop recognized the need to improve teacher in a rapidly changing world in which man must change the existing way of thinking about ourselves and build decks motivation in itself to continuing work on each other to be. Keywords: politics parents, lifelong learning.